Comparando Políticas de Desenvolvimento e Atuação do Estado. América Latina e Leste Asiático - Diogo Henrique Helal (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2013)
This paper deepens the quarrel on State-Society relations, and shows how it defines the possibilities of development, by making a comparative debate of State’s action in South Korea and Taiwan, on one side, and Brazil (mainly) and Argentina, on the other side. The East Asiatic countries are paradigmatic cases of a fast local industrialization adjustments to changeable international markets. They are active States, that worked as substitutes of capital market less developed and at the same time led to changes in investment decisions. The Asiatic case shows that the embeddedness is necessary to the dissemination of information and implementation of development politics. However, without autonomy, the embeddedness tends to degenerate in a super cartel, focused, as all cartels, on the protection of their members against changes in status quo. In your turn, the Latin America inserts itself in combination of zairense predation with a embedded autonomy from East Asia. The equilibrium changes with time, according to the type of organization inside the State. In a general way, as a basic premise, it is necessary only a vague approximation from weberian ideal type, and from embedded autonomy model (development model) to give advantage to the country.